Effects of High Impact Grazing on Species Diversity and Plant Functional Groups in Grasslands of Northern Argentina - Kurtz, Ditmar Bernardo (2018)
High impact grazing (HIG) was proposed as a management option to reduce standing dead biomass in Northern Argentinean (Chaco) rangelands. However, the effects of HIG on grassland diversity and shifts in plant functional groups are largely unknown but essential to assess the sustainability of the impact. During a two-year grazing experiment, HIG was applied every month to analyze the seasonal effects on plant species composition and plant functional groups. The results indicate that irrespective of the season in which HIG was applied, the diversity parameters were not negatively affected. Species richness, the Shannon–Wiener diversity index and the Shannon’s equitability index did not differ from the control site within a 12-month period after HIG. While plant functional groups of dicotyledonous and annual species could not benefit from the HIG disturbance, C3-, C4-monocotyledonous and perennials increased their absolute and relative green cover. Our results suggest that HIG, if not applied in shorter frequencies than a year, neither alters diversity nor shifts the plant species composition of the grassland plant community, but instead it promotes previously established rather competitive species. HIG could therefore contribute as an alternative management practice to the sustainable land use intensification of the “Gran Chaco” grassland ecosystem and even counteract the encroachment of “low value” species.